Maintaining Harmony: How Religion and Culture are Interwoven in Managing Daily Diabetes Self-Care - Permana, Iman (Journal of religion and health, 2019)
The lingering culture among Javanese people cannot be separated from religion, influencing how they perceive any factors that might play a role in managing any health condition. This present study aimed in exploring the perceptions and experiences of religion and culture in performing daily self-care among Javanese Muslim with type 2 diabetes. A qualitative study with thematic content analysis method utilizing in-depth semi-structured interviews was undertaken to explore the perceptions and experiences of Javanese Muslim with diabetes managing their daily self-care activity. Convenient samples of 24 participants were selected to gain a richer understanding of self-care activity. The study identified one main theme of maintaining harmony' with comprised of two sub-themes: surrender and accept', and keep trying and leave the rest to Allah, a concept of tawakkal'. The first sub-theme consists of categories of: nerimo ing pandum, or accepting with sincerity, and tepo seliro, or being tolerance with others. The second sub-theme consists of three categories: being independent, social ties, and embracing Allah. The study also reveals the importance of Pengajian and Persadia as social resources in enhancing the capability to better self-care the condition. Thus, it also reveals the need to further develop diabetes education programmes in collaboration with religious leaders and health professionals to promote self-care to complement religious practice: Tawakkal or Keep trying and leave the rest to Allah'.